MyOncofertility.org: a web-based patient education resource supporting decision making under severe emotional and cognitive overload - Jona, Kemi; Gerber, Adam (Cancer treatment and research, 2010)
Kristin, a 38-year-old female with breast cancer, was scheduled to begin treatment a week after receiving her diagnosis. Although she was in a four-year-long relationship, she had never thought about having kids. Kristin was told that embryo banking (IVF) was the best option for fertility preservation, and she had to decide immediately if she wanted biological children in order to start an egg-retrieval cycle. Because no other options were provided and she was uncertain about freezing embryos with her partner, she ended up foregoing fertility preservation prior to the treatments that ultimately left her infertile. Ethan, a 19-year-old male, was in the hospital for four days awaiting surgery to remove a pelvic sarcoma. The surgery required removal of his testes rendering him infertile. During those four days, no one talked to him or his family about sperm banking, even though it could hve been accomplished in a matter of minutes.